Distributional Effects of Capital and Labor on Economic Growth - Michal Paluch; Marc Schiffbauer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
In the following we propose a growth model for an economy consisting of firms which are heterogeneous in technologies and input demands. We show that the growth rate in this economy depends not only on changes in the aggregate level of capital and labor, but also on changes in the allocation of these inputs across firms. As the latter effects are neglected in conventional growth models, they are misleadingly captured by the residual TFP measure. In contrast, we are able to quantify the infuence of these components. Our empirical analysis, which is based on structural estimation from firm-level data, reveals that changes in allocation of capital and labor have pronounced effects on GDP-growth for most European countries. Further, we take cross-country differences in the distributional effects into account to improve conventional growth accounting exercises. In particular, we find that they explain additionally up to 17% of growth differences among 19 European countries. Consequently, allowing for heterogeneity in firm-level technologies and input demands increases the explanatory power of the inputs.
Keywords: 330; aggregation of production functions; distribution of capital and labor; firm heterogeneity; growth accounting; structural stability.; Wirtschaftswachstum; Produktionsfunktion; Aggregation; Allokation; Kapital; Arbeit; Produktivität; Funktionelle Einkommensverteilung; Europa